WOMEN'S REPRESENTATIVES AS GENDER EQUALITY EFFICIENCY IN LEGISLATIVE INSTITUTE / CITY IN EAST JAVA PROVINCE - Radhiyah Rahma Kartika; Regita Aprilia; Moch Ali Mashuri (PAJ, 2021)
WOMEN'S REPRESENTATIVES AS GENDER EQUALITY EFFICIENCY IN LEGISLATIVE INSTITUTE / CITY IN EAST JAVA PROVINCE